Proposing Kluyvera georgiana as the Origin of the Plasmid-Mediated Resistance Gene fosA4 - Rodriguez, Maria Margarita (2018)
A putative fosA gene in Kluyvera georgiana 14751 showed 99% nucleotide identity with plasmid-encoded fosA4. Due to a single-nucleotide insertion translating to a truncated protein, K. georgiana 14751 fosA does not confer fosfomycin resistance. However, analysis of another genome deposit (Kluyvera ascorbata WCH1410) that could be recategorized as K. georgiana after phylogenetic analysis revealed a fosA gene 100% identical to the plasmid-borne fosA4 gene. We suggest that Kluyvera georgiana represents the most probable origin of fosA4.